Land Acquisitions in Africa: A Return to Franz Fanon? - Stephan, Harry; Lobban, Ryan; Benjamin, Jessica (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: In order to understand the predicament facing Africa today, one has to return to a previous era when Africa faced its fight against colonalization. One hundred and twenty-five years after the Berlin Conference, a vast majority of African states remain in a position of social and political stagnation. Decolonization, which was supposedly based on the positive-sum incorporation of the newly-independent states into the international political arena, led to the dissolution of the rhetoric of âcivilizing the barbaric massesâ; and a new global endeavor emerged to âdevelopâ the post-colonial state via its access to the absolute gains of the global political economy. For the majority of populaces of the Third World, however, the promises of social security, economic advancement, equal terms of trade, and the abandonment of force and racism did not shadow the decolonization process. In this context, Franz Fanon said that there is nothing save a minimum of re-adaptation, a few reforms at the top, a flag waving, and down at the bottom an undivided mass still living in the middle ages, endlessly marking time. KEY WORDS: Africa today, decolonization, socio-economic and political development, and thesis of Franz Fanon.===About the Authors: Dr. Harry Stephan, Dr. Ryan Lobban, and Dr. Jessica Benjamin are the Lecturers at the University of Cape Town, Republic of South Africa. One of them can be reached at: hstephan@iafrica.comHow to cite this article? Stephan, Harry, Ryan Lobban & Jessica Benjamin. (2010). âLand Acquisitions in Africa: A Return to Franz Fanon?â in TAWARIKH: International Journal for Historical Studies, Vol.2(1) October, pp.75-92. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 20, 2010); Revised (September 25, 2010); and Published (October 28, 2010).